Analysis of IT Service Desk Applications Using the Servqual Method at The Republic of Indonesia National Library - Siti Nur Khasanah; Dewi Masyithoh (Paradigma - Jurnal Komputer dan Informatika, 2024)
The National Library has implemented an Electronic-Based Government System (SPBE) so that library service operations and operations for the national library staff have used a computerized system which results in the PERPUSNAS requiring centralized management of IT problems, namely the IT Service Desk. As an IT problem service, IT Service Desk needs to be analyzed to measure the level of user satisfaction to determine the quality of its services. In this study, the measurement of the level of user satisfaction of IT service desk services was carried out using the Servqual method which has 5 dimensions of service quality, namely Tangible, Reliability, Responsiveness, Assurance, and Emphaty by looking for the value of the gap between the value of perception and the value of expectations from users. The results of the IT Service Desk measurement at PERPUSNAS RI obtained a gap of -0.78 with the category "Good Enough".